(untitled) (Forum Penelitian Agro Ekonomi, 2016)
The adoption of modernization paradigm which majoring efficiency principle in agricultural development has caused the change in rural peasant social structure. The changes are especially related to farm land ownership creating the substratum of peasant, i.e., the upper and lower level of peasant. All peasant definitions are equal by its diametric and equip by each other, so that it needs a study in relation to its pattern change, interaction, and institution that historically experienced by the peasant society. The influencing development factors affecting peasant daily life should refer to the potential and the empowerment of the society. This is very important in order to adapt and sustain the development without losing the norms, values, and souls of indigenous knowledge. Ekonomi kerakyatan (people’s economy) concept represents the economic idea trying to formulate the interpretation base and the development aspiration of the people’s fairness and prosperity. This concept would become the peasant empowerment base for their prosperity and earnings improvement. Agricultural revitalization is needed to help improve people’s quality of life which could be achieved through: active participation of the society, skills development of human resource, improvement of landholdings title and agricultural productive assets on the basis of farm labor, technology and financial development, enhancement of rural organizations including self-help financial support, and improvement of agriculture resource-based development.